CONFLICT OF LEGAL NORMS IN TAX LAWS AND THEIR SOLUTIONS - Mulyana, Miriam Millen; Khairunnisa, Ara Hasna (JOURNAL EQUITABLE, 2025)
The existence of conflicting legal norms in tax regulations that result in legal uncertainty for taxpayers, especially in the case of the Chevron Makassar Ltd VAT dispute related to Value Added Tax (VAT) for the January to February 2009 Tax Period which was decided by the Supreme Court in its decision Number 467/B/Pk/Pjk/2022 dated March 1, 2022. The difference in interpretation between Government Regulation (PP) No. 143 of 2000, which states that VAT is collected at the time of payment, and the Minister of Finance Regulation (PMK) No. 11/PMK.03/2005, which requires VAT to be collected at the time of delivery of goods or services without waiting for payment, creates inconsistencies in the application of the law. This inconsistency creates losses for taxpayers when the Directorate General of Taxes and the Supreme Court refer to PMK which is lower in hierarchy than PP. Through normative methods, this study examines the application of the principle of lex superior derogat legi inferiori to assess the need to prioritize regulations with a higher hierarchy in order to ensure legal certainty and justice. The results of the study indicate the need for harmonization of regulations so that differences in norms do not harm taxpayers and law enforcement runs consistently. It is recommended that the government and tax authorities clarify and harmonize VAT collection regulations in order to create a fairer and more certain taxation system for taxpayers.